PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T. (The Accounting Review, 1948)
The article presents an overview of problems prepared by the Board of Examiners of the American Institute of Accounting. The problems were presented as the second half of the C.P.A. examination in accounting practice in November 1947. The candidates were allowed four and a half hours to solve both of the problems. Each problem was given a weight of 25 points. Some of the problems were to prepare information from a statement of the company's loan account with X Bank for the two months of September and October 1947, a statement showing quantities of purchased-chased materials covered by trust receipts at October 31, 1947 and a statement showing the quantity of the company's product in inventory at October 31, 1947. In the second problem, data was given and the students had to prepare, an account sales for September, 1947, as rendered by each of the three consignees, columnar work sheet showing corrections to the accounts of the Winston Company, as of September 30, 1947, and a condensed income statement of the Winston Company for the year ended September 30, 1947.